Evaluation of certain food additives and contaminants : sixty-seventh report of the Joint FAO/WHO Expert Committee on Food Additives (WHO, 2007)
The report contains a general discussion of the principles governing the toxicological evaluation and assessments of intake of food additives (in particular flavoring agents) and contaminants. A summary follows of the Committee\'s evaluations of technical, toxicological, and intake data for certain food additives (annatto extracts, natamycin, propyl paraben, synthetic lycopene and lycopene from Blakeslea trispora, and quillaia extract type 2) and food contaminants (aluminium, 3-chloro-1 2-propanediol, 1 3-dichloro-2-propanol, and methylmercury). Specifications for the following food additives were revised: carob bean gum, guar gum, titanium dioxide, and zeaxanthin. Annexed to the report are tables summarizing the Committee\'s recommendations for intakes and toxicological evaluations of the food additives and contaminants considered.
WHO technical report series, ISSN 0512-3054 940
Keywords: hodnocení rizik; potravinářské přísady; Food Contamination; zemědělství a potravinářství; toxikologie; Flavoring Agents; chuťové esence; Food Additives; Risk Assessment; kontaminace potravin; nutriční terapie, dietoterapie a výživa